Real crime, real victims: environmental crime victims and the Crime Victims’ Rights Act (CVRA) - Jarrell, Melissa L. (Crime, law and social change, 2012)
The Crime Victims’ Rights Act (CVRA) was signed into U.S. federal law in 2004 with the expressed purpose of empowering crime victims, expanding the role of the victim in federal criminal prosecutions, and providing more clearly defined roles for victims in court proceedings. As environmental crime cases have progressed through the federal court system, the courts and legal scholarship have begun to address the complexities associated with environmental crime victimization under the CVRA. This article provides an overview of recent environmental crime cases that have addressed the CVRA. It then discusses criticisms of including environmental crime victims under the CVRA, while developing a thesis in support of victim recognition.